Hepatic Adenomatosis: Diagnosis and Management Dilemma - S , Norly; J, Razman (IIUM Medical Journal Malaysia, 2010)
Hepatic adenomatosis is a rare, benign tumour of the liver. It was first described by Flejou et al as multiple adenomas in an otherwise normal liver parenchyma. Although benign, it can present as a diagnostic challenge because the lesions can be difficult to distinguish from other hepatic tumours. Patients can be asymptomatic and the diagnosis may only be made incidentally. We describe the case of 40-year-old Malay lady who was incidentally found to have hepatomegaly. Radiological examinations revealed a complex left ovarian cyst with multiple liver lesions. Biopsy of the liver lesion showed features of hepatic adenomatosis. Literature review was done and the dilemma in managing her was discussed.